ANALISIS IMPLEMENTASI DATA INFORMASI GEOSPASIAL SEBAGAI UPAYA PENINGKATAN KEBUTUHAN PERLENGKAPAN JALAN DI DINAS PERHUBUNGAN KABUPATEN PROBOLINGGO - jurnalmap map; Suhariyanto ÔÇÄ; Woro Utari (MAP (Jurnal Manajemen dan Administrasi Publik), 2020)
The purpose of this study was to find out more about how the human resources in the use of data and Geospatial Information in Probolinggo District Department of Transportation. This study uses descriptive analysis with qualitative approach, data collection techniques using the technique of the interview, observation and documentation study, primary data and secondary that was obtained in this research are collected through qualitative procedures that include reduction, and data verification or conclusion. The conclusion of this study is data about the equipment needs of a given path is not optimal due to the limited human resources and facilities are not optimal, such as the lack of application of the equipment needs of the road is used as a reference design of existing activity in Probolinggo District Department of Transportation. In addition, signs equipment on the road needs should be met as needed road because it is a very important instrument in planning towards road safety. Keywords: quality, data geospatial information